Evaluasi Kenyamanan Termal pada Bangunan Kos di Bandung melalui Pendekatan Simulasi dan Pengukuran Lapangan - Ariq Ikhsan Pradana; Muhammad Shalahuddin Husain; Yazid E. Bustomi; Nur Laela Latifah; Erwin Yuniar Rahadian; Reza Phalevi Sihombing (Arsitektura : Jurnal Ilmiah Arsitektur dan Lingkungan Binaan, 2026)
Evaluation of Thermal Comfort in Dormitory Buildings in Bandung Through Simulation and Field Measurement ApproachesThe application of passive design in tropical housing often focuses solely on shading and mass orientation, neglecting microclimate performance evaluations. This study aims to reveal thermal discrepancies in the Kost Grage building within a dense settlement in Bandung, referenced to established standards. Employing a quantitative method approach, this research combines Autodesk Forma digital simulations with field measurements (wind speed, relative humidity, and air temperature) for validation. Results indicate that the shaded East Room recorded a higher average temperature (29.16°C) compared to the West Room, which had greater exposure to solar radiation (28.31°C). The study's novelty highlights that this discrepancy is driven by adaptive user behavior; passive design strategies that optimize air openings create cross-ventilation, effectively mitigating heat and supporting the achievement of thermal comfort.